The alms bazaar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The alms bazaar: altruism under fire - non-profit organizations and international development by lan Smillie 1995 286pp ISBN 1 85339 301 0